Mispersepsi Evaluasi dalam Pengelolaan Kelembagaan Pendidikan Islam di Indonesia - Kardiyo Kardiyo; Ririn Handayani; Vera Nopianti (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: Management of educational institutions still has misunderstandings in evaluations, characterized by immature and inconsistent strategic plans because they are not balanced with budget availability, resulting in plans being left to plan, there is no ability to implement the strategic plan. The aim of this research is to evaluate misperceptions in the management of educational institutions. Using descriptive qualitative methods. The sources of information in this research use various sources, both online media data and print media data, including scientific books, national and international scientific articles. The data obtained went through several stages of data collection, data reduction, presentation, and conclusion drawing. The results of the research can be concluded that there has been a misperception of evaluation in the management of Islamic educational institutions due to a lack of understanding of the standards for managing educational institutions, resulting in misunderstanding of the provisions set out, and budget limitations, so that the programs that have been prepared cannot be implemented. Thus, it can be suggested that to avoid misperceptions, increase evaluation in the management of Islamic school education institutions in Indonesia. Keywords: Misperception, Evaluation, Islamic Education Institutions Abstrak: Pengelolaan kelembagaan pendidikan masih terjadi salah persepsi dalam evaluasi, ditandai dengan rencana strategis yang tidak matang dan tidak konsisten disebabkan tidak diimbangi dengan ketersediaan anggaran, sehingga mengakibatkan rencana tinggal rencana, tidak ada kemampuan dalam mengimplementasikan renstra. Tujuan penelitian ini untuk mengevaluasi mispersepsi dalam pengelolaan kelembagaan Pendidikan. Menggunakan metode kualitatif deskriptif. Sumber informasi dalam penelitian ini, menggunakan berbagai sumber, baik data media online maupun data media cetak, meliputi buku-buku ilmiah, artikel ilmiah baik nasional maupun internasional. Data yang didapat melalui beberapa tahapan pengumpulan data, reduksi data (data reduction), penyajian, dan penarikan kesimpulan (conclusion drawing). Hasil penelitian dapat disimpulkan telah terjadi mispersepsi evaluasi dalam pengelolaan kelembagaan pendidikan Islam disebabkan karena kurangnya pemahaman tentang standar pengelolaan kelembagaan pendidikan, sehingga terjadi salah dalam memahami ketentuan yang ditetapkan, dan keterbatasan anggaran, sehingga program yang telah disusun tidak bisa diimplementasikan. Dengan demikian dapat disarankan untuk tidak terjadi salah persepsi, maka tingkatkanlah evaluasi dalam pengelolaan kelembagaan pendidikan Islam sekolah di Indonesia. Kata kunci: Mispersepsi, Evaluasi, Kelembagaan Pendidikan Islam